APPROACHES TO COMBINED THERAPY OF ACUTE INTESTINAL INFECTIONS IN CHILDREN - N.G. Soboleva; N.Kh. Tkhakushinova ("Paediatrician" Publishers LLC, 2010)
The results of combined therapy of acute intestinal infections in children with lactulose and pancreatine in prebiotic dose are discussed in this article. Authors showed advantages of combined treatment: significant shortening of terms of symptoms stopping and children's recovery.Key words: children, acute intestinal infections, lactulose, pancreatine.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):102-106)